Chance Encounters A Bioethics for a Damaged Planet - Hens, Kristien (Open Book Publishers, 2022)
In this rigorous and necessary book, Kristien Hens brings together bioethics and the philosophy of biology to argue that it is ethically necessary for scientific research to include a place for the philosopher. As well as ethical, their role is conceptual: they can improve the quality and coherence of scientific research by ensuring that particular concepts are used consistently and thoughtfully across interdisciplinary projects. Hens argues that chance and uncertainty play a central part in bioethics, but that these qualities can be in tension with the attempt to establish a given theory as scientific knowledge: in describing organisms and practices, in a sense we create the world. Hens contends that this is necessarily an ethical activity. Examining genetic research, biomedical ethics, autism research and the concept of risk, Hens illustrates that there is no 'universal' or 'neutral' state of scientific and clinical knowledge, and that attending to the situatedness of individual experience is essential to understand the world around us, to know its (and our) limitations, and to forge an ethical future. Chance Encounters is aimed at a broad audience of researchers in bioethics, philosophy, anthropology, sociology, as well as biomedical and environmental scientists. It will also be relevant to policymakers, and the artwork by Christina Stadlbauer and Bartaku will be of interest to artists and writers working at the intersection of art and science.